Strategy To Increase Fee-Based Income Through Optimizing Sukuk Sales To Priority Customers - Indrayanti, Rr Nugraheni Putri; Nurhidayah, Nurhidayah; Alrasyid, Harun (Institut Teknologi dan Bisnis Asia Malang, 2025)
Bank Syariah Indonesia (BSI) as one of the largest Islamic banks in Indonesia has a great opportunity to increase non-interest income or Fee Based Income (FBI) by optimizing sukuk sales, especially to priority customer segments. The purpose of this research is to provide funding sources that are in accordance with sharia principles, support economic development, and offer investment alternatives for people who want halal financial products. Using a qualitative approach with the SWOT analysis method. The results of this study indicate that optimization of sukuk sales has a significant contribution to increasing Fee Based Income (FBI) at Bank Syariah Indonesia (BSI), especially in the priority customer segment in the Malang Area. However, the effectiveness of sukuk marketing strategies is still not optimal with the low understanding of priority customers regarding the benefits of sukuk investment as a sharia financial product, lack of training and competence of marketing staff in conveying the advantages of sukuk comprehensively, marketing strategies that have not been segmented properly, so they do not match the characteristics and needs of priority customers, accessibility of sukuk services digitally is not optimal, which has an impact on the convenience and ease of transactions for customers.